THE INFLUENCE OF UTILIZING CHATGPT AS A DIGITAL LEARNING MEDIA ON STUDENTS’ LEARNING MOTIVATION AND ACHIEVEMENT IN LEARNING ENGLISH (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study aims to examine the influence of ChatGPT as a digital learning media on students' learning motivation and achievement in English towards eleventh-grade students at MAN 1 Surakarta in the 2024/2025 academic year. The research employed a quantitative approach with a One-Group Pretest-Posttest design. The sample consists of 34 students selected through a random sampling technique. Data collection instruments include test and questionnaires to measure the impact of ChatGPT on students' motivation and achievement in English. Data analysis is conducted using a paired sample t-test with the assistance of the IBM SPSS Statistics 25 software. The findings reveal a statistically significant influence of ChatGPT on students’ learning motivation and achievement in English. Based on the paired sample t-test analysis, the t-count value for the questionnaire is 8.879, while for the test, it is 16.062. When compared to the t-table value at a degree of freedom (df) of 33 (n-1) with a 5% significance level (2.035), both t-count values exceed the t-table value (8.879 > 2.035 and 16.062 > 2.035). These results lead to the rejection of Ho and the acceptance of Ha, indicating that ChatGPT has a significant influence on students' motivation and academic achievement in English learning.